Adhesion and Alignment of Nonparenchymal Cells onto a Patterned Surface with a Two‐Step Plasma Polymerization Process. Issue 8 (11th February 2015) - Muguruma, Hitoshi; Hoshino, Tatsuya; Fujita, Ryosuke; Sumii, Takeki; Kudo, Susumu
<x xml:space="preserve">Abstract</x> The precise control for the micropatterning of nonparenchymal cells (endothelial cells; ECs and hepatic stellate cells; HSCs) is useful for regenerative medicine, artificial organs, and cell‐based biodevice. The adhesion and alignment of nonparenchymal cells on a micro‐patterned surface fabricated by two‐step plasma polymerization process were investigated. The first functionalization step involves the deposition of a nitrogen‐rich plasma‐polymerized film to render the entire surface a cell‐adherent region. Following this, a hydrophobic plasma‐polymerized film is formed through a grid metal mask (hundred‐micrometer‐sized openings) to renders these areas cell repellent. Imaging ellipsometry showed that groove and ridge patterns 100 μm wide and steps with heights on the scale of tens of nanometers were obtained. EC and HSC culture experiments were conducted on the patterned surfaces. EC rapidly adhered and aligned along the cell‐adherent groove of the patterned surface, while it did not adhere to the cell‐repellent ridge. HSC patterning succeeded only when the height of the cell‐repellent ridge was 20 nm, whereas the patterning failed when the ridge height was 10 nm. This indicates that EC patterning is possible with only a chemical effect, whereas HSC patterning required both a chemical effect and the topological constraints of the patterned surface.